Contributing Factors of DKA in patients of diabetes mellitus - Muhammad Rizwan Haider, Afsheen Batool Raza, Nadia Nawaz, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective is to define the occurrence of contributing factors of DKA in diabetes patients. Study design: Descriptive cross sectional Place and duration: At Institute of Child Health and Children’s Hospital Lahore study was conceded out from 1st May 2018 to 30th April 2019. Material and method: Those Patients were included in the study who were completing inclusion area. Informed agreement was taken from patients and their information was recorded. Complete medical record including non-compliance, infections and laboratory findings was also retrieved. Data was entered in Performa. Results: The recorded mean age calculated was 7.79+4.24 years, 55.5 %( n=111) were females and 44.5 %( n=89) were males. Occurrence of contributing factors of DKA in patients of diabetes mellitus was recorded as 41%(n=82) infection, frequency of type of infection was calculated as 15%(n=30) had RTI, 13%(n=26) had CNS, 13%(n=26) had UTI while 59%(n=118) had no infection. Conclusion: Frequency of infection was higher followed by non-compliance as contributing factors of DKA in patients of diabetes mellitus. However, respiratory tract infection was the commonest infection in our population.